Root-associated microbiota of decline-affected and asymptomatic Pinus sylvestris trees - Ana V. Lasa; Antonio J. Pérez-Luque; Manuel Fernández-López (Scientific Data)
Abstract Forest decline is a worldwide phenomenon affecting many species such as Pinus sylvestris. Although it is driven by multiple stressors, the role of tree associated microorganisms remains still unclear. To reduce this knowledge gap we obtained amplicon sequences of the microbiota inhabiting the rhizosphere soil and root endosphere (bacterial 16S rRNA and fungal ITS2) of decline-affected and asymptomatic P. sylvestris trees in spring and summer. The dataset comprised a total of 384 samples from three mountainous areas which yielded an average of 59,592.3 ± 7,371 and 56,894.3 ± 12,983.5 (spring and summer) bacterial and 74,827.9 ± 12,095.4 and 85,363.9 ± 14,199.3 (spring and summer) fungal raw reads, resulting in 23,982.4 ± 11,312.4 (spring) and 17,921.8 ± 10,802.7 (summer) bacterial and 50,571.1 ± 10,499.5 (spring) and 49,509.4 ± 12,673.8 (summer) fungal quality-filtered sequences. These data and the corresponding metadata could be used to identify pine decline bioindicators, to develop novel diagnosis tools of specific microorganisms and could serve as reference against which to compare other microbial communities.